2017
DOI: 10.1146/annurev-biochem-061516-044617
|View full text |Cite
|
Sign up to set email alerts
|

A Bright Future for Antibiotics?

Abstract: Multidrug resistance is a global threat as the clinically available potent antibiotic drugs are becoming exceedingly scarce. For example, increasing drug resistance among gram-positive bacteria is responsible for approximately one-third of nosocomial infections. As ribosomes are a major target for these drugs, they may serve as suitable objects for novel development of next-generation antibiotics. Three-dimensional structures of ribosomal particles from Staphylococcus aureus obtained by X-ray crystallography h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 124 publications
1
16
0
Order By: Relevance
“…CTX-M enzymes, especially CTX-M-15, are related to various epidemiological situations and have spread throughout the continents due to epidemic plasmids and/or epidemic strains [47]. Corroborating this statement, in the present study, the bla CTX-M-15 gene was found in K. pneumoniae in all continents evaluated Table (1)(2)(3)(4). Many of the emerging antimicrobial resistance problems of the nineties have been characterized by difficulty in recognition of resistance in the laboratory, particularly by rapid susceptibilitytest methods.…”
Section: Epidemiologysupporting
confidence: 77%
See 2 more Smart Citations
“…CTX-M enzymes, especially CTX-M-15, are related to various epidemiological situations and have spread throughout the continents due to epidemic plasmids and/or epidemic strains [47]. Corroborating this statement, in the present study, the bla CTX-M-15 gene was found in K. pneumoniae in all continents evaluated Table (1)(2)(3)(4). Many of the emerging antimicrobial resistance problems of the nineties have been characterized by difficulty in recognition of resistance in the laboratory, particularly by rapid susceptibilitytest methods.…”
Section: Epidemiologysupporting
confidence: 77%
“…This is responsible for a variety of diseases in humans and animals, such as urinary tract infection, pneumoniae, intra-abdominal infection, bloodstream infection, meningitis, pyogenic liver abscess and is a prominent nosocomial pathogen [1,2]. Moreover, the occurrence and global spread of hypervirulent and MDR (multidrug-resistant) K. pneumoniae are increasingly reported in communityacquired and nosocomial infections [3], and the use of antimicrobials in the treatment of infections has become progressively more difficult [4,5]. However, despite there has been an increase in the number of vulnerable populations to MDR pathogens, in addition to a renewed interest in the Klebsiella pneumoniae, many questions about this pathogen are still unknown, as to how resistance genes spread out and how they reach humans [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ribosomes have long been the target of clinically useful antibiotics. Differences found in bacterial and eukaryote ribosomes through high resolution three‐dimensional structural analysis could be exploited for next‐generation antibiotics …”
Section: Discussionmentioning
confidence: 99%
“…Differences found in bacterial and eukaryoter ibosomest hrough high resolution three-dimensional structural analysis could be exploited for next-generation antibiotics. [57] Riboswitches are ideal targets because analogueso fs mallmolecule metabolites can be used to disruptn ormal riboswitch regulation of the gene expression. Riboswitch inhibitors have been found.…”
Section: Discussionmentioning
confidence: 99%